Challenges of Transferring a Japanese Idea to the Educational Context of Iran's Primary Schools: Lesson Study Model - Abolfazl Kamali; Ali Taghipour Zahir; Reza Shabannejad Khas; Nader Gholi Ghorchian; Afsaneh Zamani Moghadam (Comparative Education Society of Iran ( CESIR), 2021)
Borrowing modern educational ideas is not an easy process for societies in transition, however, new needs and necessities have made it an inevitable decision for curriculum planners. The purpose of this article is to present the research findings that have been done qualitatively using grounded theory approach. The research population consisted of primary school teachers and the method of sampling was snowball. Unstructured interviews were used to collect data. Data analysis has led to the presentation of a semantic model and the identification of four major groups of cultural, economic, professional and educational challenges for the implementation of the Japanese model of "Lesson Study" in Iran primary schools. Also, contextual and intervening conditions have reduced teachers' interest in this model and increased their attention to competing models such as action research, futures studies and narrative research. To address these challenges and localize Lesson Study model, some of primary school teachers have used three strategies of aggressive, complementary, and diversification